Addressing Misconceptions in Biology Using Design Thinking as A Framework - Atchia, Shakeel; Charles, Heeroo E.; Hourani, Mowlabucus M. (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2025)
Despite the importance of science in our everyday life, a decline in students’ academic performances and interest towards Biology have been empirically publicized by several researchers. Though multifactorial, misconception remains one of the key factors affecting students’ understanding of concepts, exam grades and interest. Consequently, the literature is gauged with empirical research focusing on the appropriateness of different methods and strategies used to identify and clear students’ misconceptions in Biology. This case study uses a mixed epistemological stance to study the appropriateness of using the DTSICM (Design Thinking Strategy to Identify and Clear Misconceptions) model, underpinned by the Stanford’s design thinking framework, in identifying and clearing the misconception of twelve low-performing students in Biology. The findings revealed that (i) the use of design thinking-based DTSICM approach is efficient in clearing students’ misconceptions, with statistical significance at 5% level ( p>0.05), and (ii) the design thinking approach provide teachers with a formalised, context-driven, needs-based and adaptable pathway to identify and clear misconceptions of students, by engaging through the five decisive stages of the design thinking framework, namely ‘emphasize’, ‘define’, ‘ideate’, ‘prototype’ and test’.